Nasal Tip Dermoid Sinus Cyst Excision by Open Rhinoplasty Technique - Sakthivel, Pirabu; Kumar, Rajeev; Kairo, Arvind; Kumar, Rakesh; Thota, Ramya (Journal of Child Science, 2017)
Nasal dermoid sinus cysts are uncommon congenital anomalies, presenting either as cysts or sinuses with varied presentation at birth, childhood, or even adulthood. A midline nasal pit, fistula, or infected mass may be located anywhere from the glabella to the nasal columella. Preoperative radiological investigation with CT (computed tomography) and MRI (magnetic resonance imaging) scans is mandatory to rule out intracranial extension. Complete excision of the cyst along with its tract is the only definitive therapeutic modality. We present a case of nasal dermoid sinus cyst in a 3-year-old male child who underwent excision by open rhinoplasty approach.
Keywords: dermoids; nasal sinuses; open rhinoplasty